Ketelitian Pemetaan dengan Foto Udara Tunggal : Studi Kasus di Kampus UGM dan Sekitarnya. - Perpustakaan UGM, i-lib ([Yogyakarta] : Center For Food and Nutritions Studies Gadjah Mada University, 1999)
ABSTRACS In soft copy photogrammetry, a common method in generating an accurate map includes some standard procedures, ie. inner orientation, outer orientation, and absolute orientation, and the photograph should have an appropriate overlap area. This research explored the use of monoplotting method to generate a map from an aerial photograph image. The aerial Photograph covered Gadjah Mada University in the scale of 1: 10,000. Steps were followed to produce a map using monoplotting technique. Firstly, an aerial photograph was scanned and then 15 existing Ground Control Points (GCPs) were identified on the image. Secondly, parameter transformations were computed using polynomial interpolation and space resection were used to generate coordinate objects on the earth. Finally, object coordinates were evaluated against existing ground control coordinates. The research shows that monoplotting technique can be used to produce thematic map, in the scale of 1: 10 000 and in 100 dpi scanning resolution. Deviation in abscise and ordinate are 10.5 pixels and 3 pixels respectively.